PERANCANGAN DAN IMPLEMENTASI SISTEM MONITORING KEAMANAN TOKO BERBASIS INTERNET OF THINGS (IOT) DENGAN MENGGUNAKAN MIKROKONTROLER ESP32-CAM (STUDI KASUS DI TOKO STELIOS AQUATIC) - COMPUTING INFORMATIKA; Nurul Imamah; sutiyono WP; Ari Reynaldi (Program Studi Teknik Informatika FTI UNIBBA, 2022)
ABSTRACT: Store security is one of the important things in life, every human being needs a guarantee of security. As is the case with the Stelios Aquatic store, it always stores items or ornamental fish that will be sold and the money from sales in the store. When the store closes, the seller or shop owner will leave the store because the store and the owner's house are not in one building so there is a risk in the store. Store security monitoring system using the Esp32-Cam microcontroller as the device controller. Then add a PIR sensor at the entrance of a store and use telegram as a notification, so that it can monitor the store remotely and is expected to increase the security of the store more strongly. In the process of designing a store security monitoring system, it is carried out using the Software Development Life Cycle (SDLC) waterfall method with the stages of analysis, design/design, implementation/coding, and testing. The development of this system uses Arduino IDE software as a code editor application in implementing the design into a store security monitoring application with Telegram notifications. With the existence of an internet of things (IoT) based store security monitoring system using the esp32-cam microcontroller, it will make it easier to monitor stores at Stelios Aquatic.